Conceptions of Assessment: Perceptions of Physical and Health Education Teachers in Selangor, Malaysia. - Yusoff, Shahazwan Mat; Chin Hai Leng; Razak, Rafiza Abdul; Basal, Mohd Helme; Mohamad Marzaini, Anwar Farhan (Pertanika Journal of Social Sciences & Humanities, 2024)
Physical and Health Education (PHE) assessment is essential for evaluating students' knowledge, skills, and attitudes towards physical and health education. Despite the limited number of studies on conceptions of assessment, more research is needed to focus on PHE teachers in the local context. This quantitative study aims to uncover secondary school PHE teachers' conceptions of assessment by examining four variables: improvement, school accountability, student accountability, and irrelevance. The study involved 268 PHE teachers from two districts in Selangor, Malaysia. Results indicated that improvement received the highest level of agreement, while irrelevance had the lowest. A MANOVA analysis explored the effects of gender and years of teaching experience on teachers' perceptions. The analysis showed no significant gender differences, but teachers with more than 20 years of experience had a significantly different mean perception of assessment compared to all other groups, suggesting that teaching experience affects teachers' conceptions of assessment. The result of this study provides valuable insights for stakeholders in education, particularly in PHE assessment. Future research may benefit from incorporating qualitative methods to enhance the study's findings on conceptions of assessment among school teachers.